La pédagogie des opprimé·es - Freire, Paulo; Dupau, Élodie; Kerhoas, Melenn (Éditions de la Rue Dorion, 2021)
Ouvrage majeur de Paulo Freire, ce livre présente quelques aspects d'une pédagogie élaborée non seulement pour les opprimés, mais avec eux, et dans le cadre même de leur lutte perpétuelle pour affirmer leur humanité. A l'image d'autres grands pédagogues, en premier lieu Célestin Freinet, Freire rappelle que projet éducatif et projet social sont indissociables. Selon lui, le but de l'éducateur est de donner aux opprimés les moyens de construire une conscience claire de leur position, et de rechercher avec eux les moyens de transformer le monde. Écrit en 1968 au Chili, ce texte irrigue encore aujourd'hui la pensée de la pédagogie critique partout dans le monde.
Keywords: OFDIG; amériques; approches et analyses; chili; discipline; oppression; pensée pédagogique; privilèges; pédagogie; pédagogie des opprimés; régions géographiques; systèmes d'oppressions; thématiques; éducation

Deconstructing privilege: Teaching and learning as allies in the classroom - Case, Kim (Routledge, 2013)
Although scholarly examinations of privilege have increased in recent decades, an emphasis on privilege studies pedagogy remains lacking within institutions. This edited collection explores best practices for effective teaching and learning about various forms of systemic group privilege such as that based on race, gender, sexuality, religion, and class. Formatted in three easy-to-follow sections, Deconstructing Privilege charts the history of privilege studies and provides intersectional approaches to the topic. Drawing on a wealth of research and real-life accounts, this book gives educators both the theoretical foundations they need to address issues of privilege in the classroom and practical ways to forge new paths for critical dialogues in educational settings. Combining interdisciplinary contributions from leading experts in the field– such as Tim Wise and Abby Ferber– with pedagogical strategies and tips for teaching about privilege, Deconstructing Privilege is an essential book for any educator who wants to address what privilege really means in the classroom.
Keywords: amériques; approches et analyses; discipline; intersectionnalité; inégalités; justice sociale; outils; ouvrages de références; privilèges; régions géographiques; sciences de l'éducation; systèmes d'oppressions; états-unis